Correlation of Energy and Protein Consumption Levels with Physical Endurance of Rhythmic Gymnast Athletes - Soenyoto, Tommy; Mollap, Korakot; Mungpong, Juthathip (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Appearance of a gymnast will score additional point in competition. This study aimed to understand the correlation between consumption level of energy and protein with physical endurance of rhythmic gymnast athletes at Wimilia gymnasium in Semarang on 2010. This was an applied study. The study samples are 7 rhythmic gymnasts at Wimilia gymnasium in Semarang. We used total sampling technique. Our analysis found a strong correlation between independent variables and dependent variable. X?Y? = 0.97; X?Y? = 0.77; X?Y? = 0.97; X?Y? = 0.96; X?Y? = 0.94; X?Y? = 0.79; X?Y? = o, 97 and X?Y? = o, 96. Research data suggested that gymnastics Wimilia coach and rhythmic gymnast trainers were to pay more attention to the correlation between dependent variable’s static balance .